2021
DOI: 10.1002/ece3.7727
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the genetic diversity of yams (Dioscorea spp.) in China by combining phenotypic trait and molecular marker analyses

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
0
7
2
Order By: Relevance
“…Microsatellite markers proved to be effective to characterise yam germplasms worldwide (Obidiegwu et al, 2009a; Obidiegwu et al, 2009b; Siqueira et al, 2011; Tostain et al, 2006; Tamiru et al, 2015; Arnau et al, 2017; Cao et al, 2021). The present study enabled the extraction of quite high numbers of microsatellites in different yam genomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microsatellite markers proved to be effective to characterise yam germplasms worldwide (Obidiegwu et al, 2009a; Obidiegwu et al, 2009b; Siqueira et al, 2011; Tostain et al, 2006; Tamiru et al, 2015; Arnau et al, 2017; Cao et al, 2021). The present study enabled the extraction of quite high numbers of microsatellites in different yam genomes.…”
Section: Discussionmentioning
confidence: 99%
“…In Dioscoreaceae , very few SSR markers have been experimentally (wet-lab) validated (Obidiegwu et al, 2009a; Obidiegwu et al, 2009b; Andris et al, 2010; Siqueira et al, 2011; Tostain et al, 2006; Tamiru et al, 2015; Arnau et al, 2017; Cao et al, 2021), most of which are from D. alata and D. rotundata . In other species such as rice (McCouch et al, 2002), sesame (Dossa et al, 2017), and cowpea ( Vigna unguiculata ) (Jasrotia et al, 2019), a large number of markers have been identified, experimentally characterised and available for genetic studies and breeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The markers commonly used in morphological characterization of different species of the genus Dioscorea are shape, color, length, and width of the leaf; the presence of wings; the color of the peel and of the pulp; and tuber weight (Wu et al 2019;Cao et al 2021;Chen et al 2022).…”
mentioning
confidence: 99%
“…In spite of the importance of phenotypic traits for germplasm characterization, they have the limitation of being subject to environmental variations (Cao et al 2021). An alternative to mitigate this problem is associating morphological and molecular markers (Agre et al 2021).…”
mentioning
confidence: 99%